Application of Excel-VBA for computation of water quality index and air pollutant index [Penggunaan Excel-VBA untuk pengiraan indeks kualiti air dan indeks pencemaran udara] - Azman, Azid; Hafizan, Juahir; Ismail, Zainal Abidin (Malaysian Society of Analytical Sciences, 2015)
In Malaysia, there are two main indices which are Water Quality Index (WQI) and Air Pollutant Index (API). These indices are used as an indicator for the water quality and ambient air quality status of the environment. In conducting research regarding water and air quality, lots of time has been used to conduct other activities, an application to calculate the indices might come in handy. This project aims to construct an application for the computation of WQI and API using Visual Basic for Applications (VBA) available in Microsoft Excel. VBA is actually a programming language of Microsoft Excel and can be used to write programming and run through in an Excel workbook. The user only required to enter the value for each parameter and then press “OK” to automatically calculate the index. This will provide instance result without wasting time just to refer to the class standard and other formula. The application also has been used as a teaching tool for the secondary students. An environmental based race game called Young Environmental Scientist (YES) Explorace was conducted by Environmental East Coast Research Institute (ESERI) where secondary student are invited as the participant. The application not only provides early exposure to the environmental pollution, but also exposure to the application of computer sciences to the student.